2015
DOI: 10.1128/aac.03599-14
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Sensitizes Fluconazole-Resistant Candida albicans To Induce Apoptotic Cell Death by Modulating Quorum Sensing

Abstract: dQuorum sensing (QS) regulates group behaviors of Candida albicans such as biofilm, hyphal growth, and virulence factors. The sesquiterpene alcohol farnesol, a QS molecule produced by C. albicans, is known to regulate the expression of virulence weapons of this fungus. Fluconazole (FCZ) is a broad-spectrum antifungal drug that is used for the treatment of C. albicans infections. While FCZ can be cytotoxic at high concentrations, our results show that at much lower concentrations, quercetin (QC), a dietary flav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 44 publications
3
43
1
Order By: Relevance
“…6A) and the thickness of biofilm matrix (Fig. 6B) in a VVC isolate consistent with the previous results [18]. Notably, it was reported that ALS1 and HWP1 were also hypha-specific genes as the expression of former mRNA was correlated well with hyphal growth and the protein product encoded by the latter was only expressed on hyphae [51][52][53].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…6A) and the thickness of biofilm matrix (Fig. 6B) in a VVC isolate consistent with the previous results [18]. Notably, it was reported that ALS1 and HWP1 were also hypha-specific genes as the expression of former mRNA was correlated well with hyphal growth and the protein product encoded by the latter was only expressed on hyphae [51][52][53].…”
Section: Discussionsupporting
confidence: 90%
“…Intriguingly, the synergism of QCT and FCZ was independent of strain phenotype of resistance/susceptibility. As a matter of fact, most of the flavonoids were good at inhibiting the growth of FCZ-susceptible free-living cells and bad at dealing with FCZ-resistant clinical isolates and biofilms in C. albicans, but they usually performed satisfactorily in combination with FCZ in biofilm removal [18,28,35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, binding of HP to the LasR signal receptor could cause a decrease in RhlR production that could result in a decrease in the rhlAB operon and rhlI production while eliminating transcriptional repression of mvfR . Related to earlier investigations, cationic Se (Dutta and Willcox, 2014), quercetin (Singh B. N. et al, 2015), kaempferol (Vikram et al, 2010), apigenin (Nazzaro et al, 2013), and caffeic acid (Borges et al, 2014) exhibited significant anti-QS effects. They can significantly reduce the secretion of virulence factors and biofilm formation in human pathogenic bacteria.…”
Section: Discussionmentioning
confidence: 64%
“…In particular, it is lethal to cystic fibrosis patients (common genetic disorder in Caucasians) by developing mucoid in lung tissue leading to pneumonia. Opportunely, numerous plant-derived QS inhibitors have been developed and the infection rate has decreased in the past few years (Hentzer et al, 2002; Hentzer and Givskov, 2003; Singh et al, 2009b; Singh B. N. et al, 2015). However, the current anti-QS therapies often are not straightforward owing to their lower bioavailability and inadequate penetration of bacterial biofilm and thus results in significant casualties (Defoirdt et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidative (Halici et al 2005), insecticidal (Yildirim et al 2012a) and antifungal (goel et al 2011 properties of U. longissima extracts were reported. Likewise, insecticidal (emsen et al 2012, Yildirim et al 2012b), antioxidant (Atalay et al 2011, Choudhary 2011), antifungal (goel et al 2011), acaricidal (Shang et al 2014) and anticancer (Odabasoglu et al 2012, Karagoz et al 2014, Singh et al 2015 activities by some isolated U. longissima compounds were shown. Nevertheless, there is blank of knowledge in literature about studies exploring antiproliferative, oxidative and genotoxic effects of U. longissima water extract (Ule) on primary mixed glial-neuronal (PMGN) non-cancerous and human GBM U87MG cells.…”
Section: Introductionmentioning
confidence: 99%